Context is key: glucocorticoid receptor and corticosteroid therapeutics in outcomes after traumatic brain injury - Taylor, Morgan A.; Kokiko-Cochran, Olga N. (Frontiers in Cellular Neuroscience, 2024)
Traumatic brain injury (TBI) is a global health burden, and survivors suffer functional and psychiatric consequences that can persist long after injury. TBI induces a physiological stress response by activating the hypothalamic-pituitary-adrenal (HPA) axis, but the effects of injury on the stress response become more complex in the long term. Clinical and experimental evidence suggests long lasting dysfunction of the stress response after TBI. Additionally, preand post-injury stress both have negative impacts on outcome following TBI. This bidirectional relationship between stress and injury impedes recovery and exacerbates TBI-induced psychiatric and cognitive dysfunction. Previous clinical and experimental studies have explored the use of synthetic glucocorticoids as a therapeutic for stress-related TBI outcomes, but these have yielded mixed results. Furthermore, long-term steroid treatment is associated with multiple negative side effects. There is a pressing need for alternative approaches that improve stress functionality after TBI. Glucocorticoid receptor (GR) has been identified as a fundamental link between stress and immune responses, and preclinical evidence suggests GR plays an important role in microglia-mediated outcomes after TBI and other neuroinflammatory conditions. In this review, we will summarize GR-mediated stress dysfunction after TBI, highlighting the role of microglia. We will discuss recent studies which target microglial GR in the context of stress and injury, and we suggest that cell-specific GR interventions may be a promising strategy for longterm TBI pathophysiology.